Seasonal and diurnal groundwater fluctuations linked to environmental and drought variability for the Kermit dune field, Chihuahuan Desert, West Texas, United States - Alix Fournier; Caleb Fox; Steven L. Forman (Frontiers in Earth Science)
Water availability is limited in the northern Chihuahua Desert due to increasing aridity and anthropogenic disturbance. This study investigates the groundwater fluctuations in the shallow water table of the Kermit dune field, West Texas, United States, to assess the aquifer’s response to climate variability and human impact. The Kermit dune field’s aquifer may contribute up to 9% of the regional Pecos Valley Aquifer’s annual recharge. Groundwater levels were monitored in three piezometers between 2021 and 2024 in both shallow central dune areas and at the downflow transition to sand sheet deposits. Statistical analyses, using linear regression, ANOVA, and mixed effects models, revealed that central groundwater (1–3 m deep) responds to precipitation with peak rise at a 3-day lag post-rainfall, while no recharge signal was detected for deeper groundwater (5–7 m deep), likely due to the thicker vadose zone and denser vegetation cover of high water-use plants, up to 80 L/day. Both areas seemed influenced by daylight duration and exhibited consistent daily cycles (5–8 mm), suggestive of evapotranspiration influence. Over the monitoring period, groundwater levels declined by ∼1.2 m on average, likely exacerbated by the formation of a dredge pond associated with mining operations. Additionally, consistently elevated electric conductivity (EC) measured post oil or produced water spill in 2022 indicated potential long-term groundwater contamination. These results highlighted the vulnerability of the shallow unconfined Kermit dunal aquifer to climate changes and anthropogenic disturbance, with implications for regional water sustainability and land surface stability.